Location-based pay at Google - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2021)
In August 2021 Google revealed that the company was considering applying a location-based pay scheme which could lead to employees who opt to work from home permanently experiencing a pay cut of up to 25%. The policy would apply to remote workers who lived in low-cost living areas. This case covers the proposed compensation policy and asks students to evaluate the pros and cons of the policy in order to understand whether this is a desirable policy for Google to implement.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Google (Firm); Wages -- High technology industries employees -- Case studies; Telecommuting -- Case studies